MARKETING HOSPITALAR: caracterização das ações de marketing dos hospitais privados do município de São Paulo - Leiderman, Eduardo Blay [UNIFESP] (2008)
Objective: To verify the existence and to analyze the marketing actions in private hospitals in the city of São Paulo and characterize these actions, the organizational structure of the marketing area, the public target of actions, the media used and evaluate the level of importance given by hospital administrators to the application of hospital marketing concepts. Methods: Exploratory cross-sectional study, carried out by means of a survey of descriptive conclusive character, made with hospital administrators, using a questionnaire. Results: The statistical data analysis showed that the hospitals studied were clearly divided in two groups whose differencials are statistically significant: 1. good infrastructure and equipment, with a well-defined investment policy in marketing; 2. worse infrastructure and less equipment, with lower proportional investment in marketing. Conclusions: 1. The actions most used are the evaluation of patients/caregivers satisfaction, web site, dissemination of the hospital services, dissemination of the hospital with publicity material, event promotion, participation of the hospital in someone else’s events, market researches, program of relationship with doctors/patients, press release service and event sponsorship. 2. The hospital administrators attribute a level of significant importance to the application of hospital marketing concepts. 3. There is a marketing structure in most of the hospitals studied. 4. The hospitals consider as extremely or very important public: patients and relatives, doctors, collaborators, health plans and community. 5. The media most used are the most simple and of lower cost: stationery, direct mail, advertisements in magazines, direct email and advertisements in newspapers. More elaborate and more expensive media are only used by hospitals with 200 beds or more, even though in a low proportion: open TV and pay-per-view TV. 6. There is a statistically significant correlation between the higher investment in marketing and the best infrastructure. 7. Although they conceptually attribute a significant level of importance to the application of hospital marketing concepts, the studied hospitals apply this concept, in practice, in a restricted way, focusing the participation in the marketing area on issues linked basically to dissemination (advertising and publicity), communication and evaluation of public satisfaction.